The Thrall of Leif the Lucky: A Story of Viking Days - Liljencrantz, Ottilie A. (Ottilia Adelina), 1876-1910 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Thrall of Leif the Lucky: A Story of Viking Days" by Ottilie A. Liljencrantz is a historical novel likely written in the late 19th century. Set during the age of Vikings, it explores themes of valor, freedom, and the human spirit against a backdrop of Norse mythology and culture. The main character, Alwin, is an English youth captured and enslaved by Vikings, with his resilience and noble lineage strongly influencing the story. At the start of the narrative, we are introduced to the bustling city of Nidaros in the 10th century, where Vikings are a dominant force. Alwin, a young Saxon captive, is brought to the market by his captor, Gorm, and sold to a trader. Despite being bound and subjected to the harsh realities of slavery, Alwin maintains his pride and defiance. As events unfold, he encounters a fierce shield-maiden named Helga, as well as a character called Sigurd. The dynamics between these characters set the stage for themes of camaraderie and conflict, foreshadowing Alwin's struggle for identity and freedom in a world ruled by power and loyalty. (This is an automatically generated summary.)
Release date is 2003-10-01
Produced by A. Elizabeth Warren. HTML version by Al Haines.
Keywords: Historical fiction; Vikings -- Fiction; Leiv Eiriksson, -approximately 1020 -- Fiction; Discoveries in geography -- Fiction; America -- Discovery and exploration -- Fiction; Northmen -- Fiction